Analysis of recipient and graft survival after primary and second kidney transplantation - A. V. Pinchuk; N. V. Shmarina; I. V. Dmitriev; V. E. Vinogradov; A. I. Kazantsev (Вестник трансплантологии и искусственных органов, 2021)
Objective: to evaluate the 1- and 5-year graft and recipient survival after primary and second kidney transplantation, to compare the outcomes depending on the age of recipients.Material and methods. The treatment outcomes for 364 patients who underwent kidney transplantation at Sklifosovsky Research Institute of Emergency Care, Moscow over the period from 2007 to 2019. Of these, 213 patients underwent kidney transplantation for the first time, while 151 patients were having a second transplantation. We analyzed the effect of previous transplants, as well as the age of the recipients on long-term survival rates.Results. No significant difference in 1- and 5-year survival of kidney recipients after primary and second transplantations was found. In contrast, the long-term graft survival significantly depended on this criterion and turned out to be significantly higher after primary transplantations. The 1- and 5-year survival of older recipients was lower than the survival of younger recipients after primary and second kidney transplantation. The 1-year graft survival after primary kidney transplantation was higher in young recipients than in older recipients of the same group, however, but there were no significant differences in the 5-year graft survival. After second transplantations, there were no significant differences in the 1- and 5-year graft survival depending on the age of recipients.Conclusion. A history of previous transplantation is an important factor in kidney transplantation outcome, which must be taken into account in clinical practice.